Pengaruh Harga dan Keragaman Produk terhadap Keputusan Pembelian Kosumen pada Toko Jihan Fashion di Tasikmalaya - Maulida Fitria; Gian Fitralisma; Asep Kosasih (Yayasan Literasi Sains Indonesia, 2024)
This study aims to determine: How big is the significant influence between price on consumer purchasing decisions, how big is the significant influence between product diversity on consumer purchasing decisions, and how big is the interactive influence between price and product diversity on purchasing decisions at Jihan Fashion Store. The research method used is a quantitative method. The number of samples in this study was 60 respondents. The results of this study indicate that: there is a positive influence of price perception on purchasing decisions. This is evidenced by the results of the t-test statistics (0.424> 0.05), with a calculated t value (4.307)> t table (1.672). There is a positive influence of product diversity on purchasing decisions. This is evidenced by the results of the t-test statistics (5.570> 1.672) the regression coefficient has a positive value of 0.795. From the F test in table 3.15, a F-calculation value of 115.535 was obtained. The above shows that Fcalculation (115.535) > Ftable (3.15), the probability of significance is 0.000. So Ho is rejected and Ha is accepted, meaning that Price, Product Diversity together have a significant effect on purchasing decisions at Jihan Fashion Store by 0.795 or 79.5%.